2013
DOI: 10.1002/fuce.201200231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Experimental Conditions on Reliability of Carbon Tolerance Studies on Ni/YSZ SOFC Anodes Operated with Methane

Abstract: The effect of experimental parameters on carbon accumulation in the Ni/YSZ anode of SOFC operated at 1,073 K with CH4, has been described in this paper. Experimental parameters including sealing of the cell to the cell holder, operating current, surface coverage by current collector paste on the surface of the anode, and the configuration of the current collector were evaluated in terms of carbon accumulation at the Ni/YSZ anode. The carbon accumulation was quantified using temperature‐programmed oxidation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The paper referred to above also showed that the coverage of silver current collector paste can have a large effect on carbon deposition, even completely preventing it if the electrode is completely covered. 473 Presumably, this works in a similar way to the barrier layer concept discussed in section 6.2. There has also been considerable controversy over the use of platinum current collectors, with claimed high power densities in dry methane for some MIECs being shown to be almost entirely due to the use of platinum current collectors and doped ceria electrolytes.…”
Section: Reflections On Experimental Workmentioning
confidence: 94%
See 1 more Smart Citation
“…The paper referred to above also showed that the coverage of silver current collector paste can have a large effect on carbon deposition, even completely preventing it if the electrode is completely covered. 473 Presumably, this works in a similar way to the barrier layer concept discussed in section 6.2. There has also been considerable controversy over the use of platinum current collectors, with claimed high power densities in dry methane for some MIECs being shown to be almost entirely due to the use of platinum current collectors and doped ceria electrolytes.…”
Section: Reflections On Experimental Workmentioning
confidence: 94%
“…It has been shown that leaks causing an increase in measured OCV of less than 0.02 V from 1.223 to 1.239 V in dry methane results in a decrease in implied water content (as calculated from the H 2 /O 2 equilibrium) of 30% from 0.24% to 0.17%. 473 This is enough to result in a dramatic decrease by over half in the amount of carbon deposition over a period of 1 h. Likewise, many groups using 10−50 μm CGO and CSO electrolytes report OCVs below 0.9 V, which implies a substantial oxygen flux at OCV through the electrolyte caused by the electronic conductivity of doped ceria (or through a slightly permeable electrolyte). This oxygen flux or leakage should be extremely effective at preventing carbon deposition and improving sulfur tolerance, but if the aim is to study the carbon and sulfur tolerance of the electrode materials then care should be taken to account for this.…”
Section: Reflections On Experimental Workmentioning
confidence: 99%
“…[52] Delamination of the electrode due to carbon deposits promoted by cell polarisation in (co-) electrolysis conditions has been reported previously. [17,55] Structural differences on the interface between the electrode and the electrolyte are examined in Fig.…”
Section: Change Of the Microstructurementioning
confidence: 79%
“…The effects of the current collector configuration on the carbon formation when the cell is operated with methane has been reported previously. [52] It is important to note that the non-porous region of the current collection may affect the partial pressures of the gases on the electrode and hence the tendency for carbon formation in these places.…”
Section: The Effect Of Fuel-compositionmentioning
confidence: 99%
“…The OCV was measured with dry H 2 in step 7 for the purpose of checking for cell failure. Finally, note that N 2 was used at the cathode during steps 4e6 to prevent unintended carbon removal via O 2 crossover [39,40]. In this work, cell failure was defined by conditions that indicate combustion: a drop in OCV with dry H 2 and an increase in the cell temperature.…”
Section: Carbon Deposition Thresholdmentioning
confidence: 99%